Vers une industrialisation de la formation à distance à l'université - Marc Trestini; Bernard Coulibaly (Centre National d'Enseignement à Distance, 2014)
After defining the concept of industrialization training in general, as well as those concepts that underlie and characterize them in this paper, we'll show how the current production process and monitoring of distance learning tend to industrialize ( i.e. meet the characteristics of the concept). We'll do this by reporting on research conducted between 2010 and 2012 at the University of Strasbourg. The objective of this research was to analyze such a process at work and measure its impact on the uses and the users of the EAD. The questions we try to answer in this paper are: why and how(precisely) this change has been made, what ideas led prescribers to review how to design et to produce distance learning, how these changes have been experienced by the different actors (education officials, teachers, students) and how they have changed the uses of technology for teaching and practices of teachers and students). Are they satisfied with this new device? Do these reconfigured devices correspond to their needs? What conclusions can be drawn?